Comparison of mutation profile between primary phyllodes tumors of the breast and their paired local recurrences - Mitus, Jerzy; Adamczyk, Agnieszka; Majchrzyk, Kaja; Kowalik, Artur; Ryś, Janusz; Niemiec, Joanna (Polish Journal of Pathology, 2020)
Phyllodes tumor of the breast (PTB) is a rare neoplasm and accounts for 0.2-2.0% of breast cancer in women. Histopathological diagnosis of the tumor is difficult, and histological features do not always predict the course of the disease and the risk of progression. Pathogenesis and molecular biological characteristics as well as PTB prognostic factors are unknown. In search for genetic factors affecting PTB progression, 10 patients were analyzed for whom material from the primary tumor and local recurrence was available. DNA isolated from paraffin blocks was sequenced using the next-generation sequencing method (NGS). In 4 pairs, consisting of primary tumor and local recurrence, probably pathogenic/pathogenic variants were detected, and in three pairs they were observed in the CDKN2A gene, while other variants were found in PTEN and TP53 genes. NGS results indicate that the above-mentioned variants are hereditary, which suggests that the CDKN2A gene might be involved in cancerogenesis of PTB. Additionally, the selected pathogenic variant of EGFR gene was exclusively detected in one recuurent tumor, which might suggest the involvement of this gene in the mechanism of progression. In order to determine if this variant is associated with progression, the frequency of this mutation should be examined in larger group of malignant and borderline tumors.